1999
DOI: 10.1080/j.1440-1614.1999.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Attachment: Convergent Validity of the Adult Attachment Interview and the Parental Bonding Instrument

Abstract: Attachment information obtained from the PBI and the AAI is comparable in participants with optimal attachment histories, but not in participants showing idealisation or anger towards their mothers. Caution is, therefore, advisable when using the PBI to obtain attachment information in clinical samples where suboptimal attachment histories are likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 23 publications
1
27
0
3
Order By: Relevance
“…However, promising findings in assessing retest reliability of the PBI suggest that the parental evaluation is a considerably stable measure, not affected by confounding variables like dysthymia, neuroticism, depressive episode, or sex (Plantes et al, 1988;Parker, 1990;Lizardi and Klein, 2005;Wilhelm et al, 2005). Furthermore, good validity of the PBI can be concluded from high agreement between sibling ratings (Parker, 1990) as well as from high correlations with according scales in the Adult Attachment Interview (Manassis et al, 1999). Further, although we have shown that total gray matter volume is not affected by this set of prenatal and postnatal factors, we cannot exclude the possibility that other regions beside the hippocampus are similarly affected.…”
Section: Discussionmentioning
confidence: 99%
“…However, promising findings in assessing retest reliability of the PBI suggest that the parental evaluation is a considerably stable measure, not affected by confounding variables like dysthymia, neuroticism, depressive episode, or sex (Plantes et al, 1988;Parker, 1990;Lizardi and Klein, 2005;Wilhelm et al, 2005). Furthermore, good validity of the PBI can be concluded from high agreement between sibling ratings (Parker, 1990) as well as from high correlations with according scales in the Adult Attachment Interview (Manassis et al, 1999). Further, although we have shown that total gray matter volume is not affected by this set of prenatal and postnatal factors, we cannot exclude the possibility that other regions beside the hippocampus are similarly affected.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PD or some temperamental traits independent from panic could influence the recall of qualitative but also quantitative features of the attachment relation [54]; generally speaking, it is possible that patients with emotional pathologies tend to search for the cause of their anxiety symptoms in their early relations with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents indicate the degree to which they agree or disagree with 25 statements using a 4-point Likert scale. PBI ratings have been corroborated by reports and interviews with siblings and parents (Parker, 1990) and differ by adult attachment classification (Manassis, Owens, Adam, West, & Sheldon-Keller, 1999). Because children's responses to the mother and father versions were highly correlated (r = .76, p < .001) and because the current study involved parents of both genders, children's responses to the mother and father versions of the questionnaire were averaged to create a composite score of parental warmth (M = 3.37, SD = .56).…”
Section: Child Attachment Interview the Child Attachment Interview (mentioning
confidence: 99%